Enhanced testicular antioxidant capacity in streptozotocin-induced diabetic rats - Protective role of vitamins C and E and selenium - Naziroglu, M (Humana Press Inc, 2003)
Diabetes mellitus is associated with diabetic impairment of testicular function, ultimately leading to reduced fertility. Its etiology may involve oxidative damage by reactive oxygen substances, and protection against this damage can be offered by antioxidant supplementation. The aim of this study was to investigate the effects of intraperitoneal administration of vitamin C and E, selenium (Se), and vitamin E plus Se (COM) on concentrations of lipid peroxide (as malondialdehyde; NIDA), reduced glutathione (GSH), and vitamin E concentrations and glutathione peroxidase (GSH-Px) activity in the testes of rats with diabetes induced by streptozotocin (STZ). Sixty groups were used (10 animals each) and these animals were initially allocated to two groups: control group and diabetic group. The diabetic group was subdivided into five groups as follows: diabetic control (DC), vitamin E, Se, COM, and vitamin C. Animals in the DC group and vitamin C, vitamin E, Se, and COM groups were made diabetic by the injection of STZ on 4 d after an injection of vitamins C and E, Se, and COM. Those vitamins and Se were also administered for 21 consecutive days. The MDA, vitamin E, GSH levels, and GSH-Px activities in testes were determined. Although the vitamin E concentration was higher in the control than in the DC group, the MDA levels were found to be lower in the control than in the DC group. The MDA levels in the testes samples of vitamin C, vitamin E, Se, and COM groups were lower than the DC group. However, GSH-Px activity and GSH levels in the testes were not significantly different between the control and DC groups. Vitamin E concentrations in the vitamin C, vitamin E, Se, and COM groups and GSH levels and GSH-Px activities in the Se, COM, and vitamin C groups were higher than either the control or DC group. The results indicate that reactive oxygen substances may be involved in possible testicular complications in diabetes of rats. Administration of vitamins C and E and Se reduced the testicular lipid peroxidation; these vitamins and Se had significant protective effects on testes of rats against oxidative damage in diabetes.
Keywords: Vitamin Q vitamin E; selenium; diabetes; lipid peroxidation; testes